An Analysis of the Implementation of Islamic Brotherhood Value on the Students of MTsN Jeurela Sukamakmur - Rahmi, Aulia (SCAD Independent, 2018)
Since the development of technology, especially school children more preoccupied by the sophisticated tools than hanging out, playing with his friends, they tend to spend hours with HP or play to play internet cafe on the need to stay in touch, learn even the Koran. This research was conducted in MTsN Jeurela Sukamakmur. This type of the research that the researchers use is a descriptive research design, data collected by using the techniques of observation, interviews and documentation. The results of this study indicate that the implementation of ukhuwah Islamiah (brotherhood) to the students of MTsN jeurela Sukamakmur cannot be said to be strong, because there are still some of the students of who do not uphold the values of brotherhood among all peoples, and the lack of understanding of students about the importance of brotherhood in life and communities that are not nice is a main factor of weak implementation of Islamic Brotherhood to the students of MTsN Jeurela Sukamakmur. Thus, there are many ways to infuse the value of brotherhood by encouraging the students of Jeurela the benefits of solidarity in Islam, giving money to charity, raising fund to be distributed to the needy, etc.